Comparison of the genetic basis of biofilm formation between Salmonella Typhimurium and Escherichia coli. Issue 11 (3rd November 2022) - Holden, Emma R.; Yasir, Muhammad; Turner, A. Keith; Charles, Ian G.; Webber, Mark A.
Abstract : Most bacteria can form biofilms, which typically have a life cycle from cells initially attaching to a surface before aggregation and growth produces biomass and an extracellular matrix before finally cells disperse. To maximize fitness at each stage of this life cycle and given the different events taking place within a biofilm, temporal regulation of gene expression is essential. We recently described the genes required for optimal fitness over time during biofilm formation in Escherichia coli using a massively parallel transposon mutagenesis approach called TraDIS- Xpress . We have now repeated this study in Salmonella enterica serovar Typhimurium to determine the similarities and differences in biofilm formation through time between these species. A core set of pathways involved in biofilm formation in both species included matrix production, nucleotide biosynthesis, flagella assembly and LPS biosynthesis. We also identified several differences between the species, including a divergent impact of the antitoxin TomB on biofilm formation in each species. We observed deletion of tomB to be detrimental throughout the development of the E. coli biofilms but increased biofilm biomass in S . Typhimurium. We also found a more pronounced role for genes involved in respiration, specifically the electron transport chain, on the fitness of mature biofilms in S . Typhimurium than in E. coli and this was linked to matrix production. This work deepens understanding of the core requirements for biofilm formation in the Enterobacteriaceae whilst also identifying some genes with specialised roles in biofilm formation in each species.